If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 2 = 10x + -3 Reorder the terms: 2 + 5x = 10x + -3 Reorder the terms: 2 + 5x = -3 + 10x Solving 2 + 5x = -3 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. 2 + 5x + -10x = -3 + 10x + -10x Combine like terms: 5x + -10x = -5x 2 + -5x = -3 + 10x + -10x Combine like terms: 10x + -10x = 0 2 + -5x = -3 + 0 2 + -5x = -3 Add '-2' to each side of the equation. 2 + -2 + -5x = -3 + -2 Combine like terms: 2 + -2 = 0 0 + -5x = -3 + -2 -5x = -3 + -2 Combine like terms: -3 + -2 = -5 -5x = -5 Divide each side by '-5'. x = 1 Simplifying x = 1
| 55n^2-52n+12=0 | | 21.8x=124.26 | | dx+dx=f | | 98-4e=-11e | | w^2-9w+30=0 | | 7(7c+1)-4c=13(13c-2) | | 1290= | | 21h^2+72-48=0 | | ((x+3))=2 | | 34x-2=45+5x | | 34x-2=45+5 | | 2.5=1.5+5h | | 3+8(2n+1)=11+16m | | 6x+7=8x-3 | | (x+3)+(-x-4)= | | crap=love | | -9+4y=3y | | ILoveU=hater | | -18=42+4y | | p+p=f | | 34-5n=12n | | -3+7v=-17 | | 35=-5c-20 | | 6x+8=4x+20 | | l+c=L | | 2c+32=44 | | 2b=80-8 | | 9(4b-2)=2(9b+3) | | (10x+3)+(-4x-2)= | | .03p=7.5+.08p | | V=BRJ | | 2x^3-x^2-20x+5=0 |